The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3201/eid2503.180894
|View full text |Cite
|
Sign up to set email alerts
|

SNP-IT Tool for Identifying Subspecies and Associated Lineages ofMycobacterium tuberculosisComplex

Abstract: The clinical phenotype of zoonotic tuberculosis and its contribution to the global burden of disease are poorly understood and probably underestimated. This shortcoming is partly because of the inability of currently available laboratory and in silico tools to accurately identify all subspecies of the Mycobacterium tuberculosis complex (MTBC). We present SNPs to Identify TB (SNP-IT), a single-nucleotide polymorphism–based tool to identify all members of MTBC, including animal clades. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 30 publications
1
59
0
Order By: Relevance
“…bovis (not intrinsically resistant to pyrazinamide)." M. orygis has been isolated from many different animals, and there is a growing recognition that it is a zoonotic source of human TB (27). Our in silico typing approach confirmed that M. orygis could be specifically identified by a mutation at codon 329 of gyrB (8).…”
supporting
confidence: 65%
“…bovis (not intrinsically resistant to pyrazinamide)." M. orygis has been isolated from many different animals, and there is a growing recognition that it is a zoonotic source of human TB (27). Our in silico typing approach confirmed that M. orygis could be specifically identified by a mutation at codon 329 of gyrB (8).…”
supporting
confidence: 65%
“…The VCF files containing SNPs for each of the samples were submitted to the SNP-IT program to detect M. tuberculosis lineages for the samples 40 .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we improve the resolution of known sub-lineages, for instance 4 We define a SNS barcode (95 SNS) that allows the rapid assignment of Mtb sub-lineage designations with detailed semantic and hierarchical sub-lineage naming schema from genomic data (.vcf files) [8][9][10] . Along with this, we provide a software package and comparative tables / figures to facilitate the interchange between five SNS schemas and three Mtb sub-lineage naming systems [8][9][10]20 . We expect these tools to facilitate the use of the expanded Mtb classification by scholars of Mtb evolution and public health practitioners alike for applications such as the rapid assessment of potential outbreaks and isolate triage for detailed phylogenetic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a python module (https://github.com/farhat-lab/fast-lineage-caller) that takes as input a .vcf file and returns the lineage / sub-lineage calls. We provide five SNS schemes for Mtb : Coll et al 8 (all lineages), the Shitikov et al 9 (L2), Stucki et al 10 (L4, geographically bounded and unbounded sub-lineages), Lipworth et al 20 ( Mtb complex species, Mtb main lineages) and the one proposed here (L1-4).…”
Section: A Python Lineage Callermentioning
confidence: 99%